Zad.1
a) (a+b)-(2a-b)-(a-2b)
b)(3x-y+1)(x+y)+(y-x)
c) -(x+ny)-(3kx+2ny)+(5kx-3ny)
zad.2
a) abc-(abc-(-xyz-(xyz-abc)))
b)s do potęgi 2 -(s do potęgi 2t-(st do potęgi 2 -s do potęgi 2)))
c)x do potęgo 2 yz-(xy do potęgi 2 z-(xyz do potęgi 2-(xyz do potęgi 2 yz-xy do potęgi 2 z )))

1

Odpowiedzi

2010-01-11T22:14:37+01:00
A) (a+b)-(2a-b)-(a-2b)=a+b-2a+b-a+2b=-2a+4b
b)(3x-y+1)(x+y)+(y-x)=3x²+3xy-xy-y²+x+y+y-x=3x²-y²+2xy+2y
c) -(x+ny)-(3kx+2ny)+(5kx-3ny)=-x-ny-3kx-2ny+5kx-3ny=-x-6ny+2kx
a) abc-(abc-(-xyz-(xyz-abc)))=abc-(abc-(-xyz-xyz+abc))=abc-(abc+xyz+xyz-abc)=abc-abc-xyz-xyz+abc=abc-2xyz
b)s do potęgi 2 -(s do potęgi 2t-(st do potęgi 2 -s do potęgi 2)))=s²-(s²t-st²+s²)=s²-s²t+st²-s²=st²-s²t